2020
DOI: 10.1002/pc.25740
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale analysis of short glass fiber‐reinforced polypropylene under monotonic and fatigue loading

Abstract: Short fiber-reinforced polypropylene is largely used in the automotive industry. Fatigue failure is one of the most failure modes observed in this class of materials. In order to better understand the damage mechanisms and plasticity evolution, this article provides an overall experimental investigation of the mechanical properties of a PPGF40 composite (polypropylene matrix reinforced by a 40% weight content of short glass fibers) including monotonic and cyclic loading. The effect of various parameters such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The same phenomenon has also been experimentally observed by Imaddahen. 38 Despite the fact that specimens in various orientations degraded globally in a similar manner, the 0° specimens ruptured at a significantly lower degradation degree than the specimens at the other orientations. This indicates a more concentrated damage distribution in the 0° specimens due to their higher stiffness in the loading direction.
Figure 5.Measured elastic stiffness (a) and stiffness degradation (b) in load-unload tests on specimens with three orientations (0°, 45°, 90°).
…”
Section: Resultsmentioning
confidence: 92%
“…The same phenomenon has also been experimentally observed by Imaddahen. 38 Despite the fact that specimens in various orientations degraded globally in a similar manner, the 0° specimens ruptured at a significantly lower degradation degree than the specimens at the other orientations. This indicates a more concentrated damage distribution in the 0° specimens due to their higher stiffness in the loading direction.
Figure 5.Measured elastic stiffness (a) and stiffness degradation (b) in load-unload tests on specimens with three orientations (0°, 45°, 90°).
…”
Section: Resultsmentioning
confidence: 92%
“…Experimental studies revealed that damage evolution inside the polymer matrix and the resulting stiffness degradation of the composite material is indeed influenced by the load amplitude [99][100][101]. Moreover, a recent study of Imaddahen et al [102] reports that the fatigue process in short-glass fiber reinforced polypropylene depends on the strain rate or frequency. They observed an improvement of the fatigue strength at higher frequencies, i.e., a higher number of bearable load cycles at higher frequencies.…”
Section: Materials Modelmentioning
confidence: 99%
“…Meanwhile, the failure modes change from fiber pull-out to fiber breakage with increasing strain rate. Imaddahen et al 8 demonstrated that the ultimate stress and Young's modulus are highly sensitive to the strain rate. Brown et al 9 investigated the strain rate-dependent mechanical behavior of E-glass/polypropylene woven fabric composite.…”
Section: Introductionmentioning
confidence: 99%